Study on Optimization of the Dedusting Air Duct Layout in Coal Mine Roadway - Zhang, Huangqing; Liu, Rong; Chun, Junwei; Xue, Quanwen; Fan, Jinyang (Frontiers in Earth Science, 2022)
Coal dust pollution in fully mechanized coal mining in coal roadway not only affects the safety production of coal mine, but also threatens the health of workers. In order to reduce dust pollution and improve the construction environment, the layout of the dedusting air duct in the dry dust collector and the influence of the duct position on the dust-producing area were studied. In addition, the effects of different cutting positions on dust removal efficiency were also studied. A full-scale model of mine roadway is established by CFD, and the influence of the position of the dedusting air duct on dust diffusion and the distance between the tunneling head and the dedusting air duct on dust removal efficiency are studied. The results show that the higher the cutting position, the higher the dust concentration, and the longer the dust diffusion time in the roadway. When the distance between the dedusting air duct and the tunneling head is set to 4m or 5m, the dust removal efficiency is the highest. Moreover, the dust removal efficiency of the dry dust collector with the dedusting air duct arranged on the opposite side of the roadway is higher than that of the collector with the duct in the middle of the roadway.